2018
DOI: 10.1002/lary.27343
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology of sensorineural hearing loss in jugular foramen paraganglioma

Abstract: 4 Laryngoscope, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…As reported before, TJP patients characteristically show a combined hearing loss [ 14 , 22 , 23 ]. Comparing the functional results according to the audiology findings, there was no relevant difference between the conventional and laser surgery group after retroauricular and infratemporal fossa type A approach.…”
Section: Discussionmentioning
confidence: 91%
“…As reported before, TJP patients characteristically show a combined hearing loss [ 14 , 22 , 23 ]. Comparing the functional results according to the audiology findings, there was no relevant difference between the conventional and laser surgery group after retroauricular and infratemporal fossa type A approach.…”
Section: Discussionmentioning
confidence: 91%
“…Given that the JF region is in close proximity to the middle ear cavity, structural anomalies or lesions arising in close proximity to this region may consequently contribute to the development of PT. 18 This study demonstrated a comprehensive analysis of associated structural abnormalities or lesions surrounding the JF region in patients with PT, which may be beneficial for appreciation of the clinico-radiological characteristics and potentially aid in decision-making for patients with PT.…”
Section: Discussionmentioning
confidence: 99%
“…28 Although PT can be present as one of the symptoms in patients with JF tumors, it rarely emerged as the first or major symptom. 18…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another hypothesis may involve changes to local vasculature as a result of these lesions. Isaacson et al (9) have proposed occlusion of the inferior cochlear vein as a pathophysiologic mechanism for sensorineural hearing loss in jugular foramen paragangliomas that did not show cochlear invasion or direct eighth nerve involvement.…”
Section: Discussionmentioning
confidence: 99%